Mary Crosse project: systematic reviews and grading the value of neonatal tests in predicting long term outcomes - Khan Khalid S; Morris Rachel K; Malin Gemma L (BMC, 2009)
Abstract Background Events before birth, condition at birth, events immediately following birth, and condition in early childhood are linked together, and have implications for health and disease in adulthood. At present, there is lack of clarity about the tests that purport to link these various stages. This is partly because there is paucity of collated information about the best strategies for predicting longer-term outcomes before (using tests in fetal period) or after birth (using tests in neonatal period, infancy as well as early childhood). Methods/Design A series of systematic reviews and meta-analyses will be undertaken to determine, amongst neonates, the ability of various tests and measures to predict infant, childhood and adult outcomes. We will search Medline, Embase, Cochrane Library, MEDION, citation lists of review articles and eligible primary articles and will contact experts in the field. Independent reviewers will select studies, extract data and assess study quality according to established criteria. Language restrictions will not be applied. Data synthesis will involve meta-analysis (where appropriate), exploration of heterogeneity and publication bias. Evidence collated will be graded for its quality to support decision making. Discussion The project will collate, synthesise and evaluate the available evidence concerning the value of tests of neonatal wellbeing to predict long term outcomes. The systematic reviews will assess the quality of available evidence and identify tests with the strongest association with outcomes, and assess their economic value. The output of this project will help formulate practice recommendations.